2014
DOI: 10.1016/j.tiv.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of immunotoxicity induced by chemicals in human precision-cut lung slices (PCLS)

Abstract: Occupational asthma can be induced by a number of chemicals at the workplace. Risk assessment of potential sensitizers is mostly performed in animal experiments. With increasing public demand for alternative methods, human precision-cut lung slices (PCLS) have been developed as an ex vivo model. Human PCLS were exposed to increasing concentrations of 20 industrial chemicals including 4 respiratory allergens, 11 contact allergens, and 5 non-sensitizing irritants. Local respiratory irritation was characterized a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
58
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(58 citation statements)
references
References 64 publications
0
58
0
Order By: Relevance
“…They form an attractive alternative to human epithelial cell cultures, since they contain all cell types in their in situ environment. Lauenstein et al reported on the use of human PCLS for chemical-induced toxicity, but concluded that it was not suitable for simple screening (Lauenstein et al, 2014). Use of this method is limited by the complex 3D structure of the model, the variable life span of the different cell types cultured, and the requirement for regular availability of fresh (healthy) human lung tissue.…”
Section: Precision Cut Lung Slicesmentioning
confidence: 99%
“…They form an attractive alternative to human epithelial cell cultures, since they contain all cell types in their in situ environment. Lauenstein et al reported on the use of human PCLS for chemical-induced toxicity, but concluded that it was not suitable for simple screening (Lauenstein et al, 2014). Use of this method is limited by the complex 3D structure of the model, the variable life span of the different cell types cultured, and the requirement for regular availability of fresh (healthy) human lung tissue.…”
Section: Precision Cut Lung Slicesmentioning
confidence: 99%
“…Human precision-cut lung slices (PCLS), an ex vivo model consisting of all relevant cell types in their microanatomical environment (de Kanter et al, 2002), are well-established in pharmacological testing (Sturton et al, 2008), analysis of allergic immune responses (Wohlsen et al, 2003) and studies of xenobiotic metabolism (Lauenstein et al, 2014). There is also emerging literature concerning the use of ex vivo lung perfusion as a tool for experimental research (Nelson et al, 2014).…”
Section: Ex Vivo Lung Modelsmentioning
confidence: 99%
“…[1][2][3][4][5] Multiple studies have focused on assessing various characteristics of cultured PCLS, such as measurement of bronchoconstriction [6][7][8] and vascular responses 9,10 induced by various stimuli. In addition, PCLS have been used to evaluate allergy, 11 asthma, 6 toxicology, [12][13][14] and infectious disease responses. 15 The anatomical architecture of PCLS also allows for studying early inflammatory and immune responses that occur in the lung.…”
Section: Introductionmentioning
confidence: 99%